SOSIALISASI PEMBELAJARAN MENDALAM UNTUK GURU DI SD INPRES PACCINONGANG - Salwa Rufaidah; Andi Muafiah Nur; Abdul Khaliq Ahmad; Anniswah Firdaus; Nurul Rofika (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This Community Service (PKM) activity aims to improve the pedagogical competence of teachers at SD Inpres Paccinongang through the socialization of Deep Learning strategies. The main problem found in partner schools is the dominance of conventional teaching methods that limit students' critical analysis skills in the digital era. This activity is part of the Teaching Skills Stabilization (PKM) course of the Master of Basic Education Program at Universitas Muhammadiyah Makassar. The implementation method is carried out through three stages: planning (observation), implementation (socialization and Q&A), and reporting (evaluation and reflection). The results of the activity show that this socialization successfully provided practical understanding to teachers regarding active student engagement techniques and innovative teaching content design. Teachers showed high enthusiasm in discussing solutions to instructional challenges in the classroom. In conclusion, this activity is effective in transforming the teacher's role into a learning facilitator capable of sharpening students' cognitive intelligence and character deeply. Continuous mentoring is recommended so that the implementation of deep learning can run consistently in schools.